2012
DOI: 10.1097/acm.0b013e318248e5c2
|View full text |Cite
|
Sign up to set email alerts
|

Handoffs in the Era of Duty Hours Reform

Abstract: With changes in the Accreditation Council for Graduate Medical Education (ACGME) Common Program Requirements related to transitions in care effective July 1, 2011, sponsoring institutions and training programs must develop a common structure for transitions in care as well as comprehensive curricula to teach and evaluate patient handoffs. In response to these changes, within the Duke University Health System, the resident-led Graduate Medical Education Patient Safety and Quality Council performed a focused rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…• Projects are being shared and published in peer-reviewed venues and academic journals, [9][10][11][12][13][14][15][16][17][18][19][20] and several others are in preparation for submission or awaiting journal decisions. A few institutions have responded by providing seed money to allow teaching faculty time for educational innovation.…”
Section: Impactsmentioning
confidence: 99%
“…• Projects are being shared and published in peer-reviewed venues and academic journals, [9][10][11][12][13][14][15][16][17][18][19][20] and several others are in preparation for submission or awaiting journal decisions. A few institutions have responded by providing seed money to allow teaching faculty time for educational innovation.…”
Section: Impactsmentioning
confidence: 99%
“…There is a consensus that the greater the number of handoffs, the greater the risk for medical errors. In order to mitigate these risks, the study calls for increased supervision and training in handoffs (DeRienzo 2012). Experts suggest that handoff-related risk can be managed by structuring a sign-out process (Bump et al 2011).…”
Section: An Alternative To the Current Systemmentioning
confidence: 99%
“…[13][14][15] Handoffs are meant to provide continuity of care and high-quality and safe decision making. Issues related to "patient handoffs" have been the focus of some recent studies.…”
Section: Physician-to-physician (Peer-to-peer) Communicationmentioning
confidence: 99%
“…Issues related to "patient handoffs" have been the focus of some recent studies. 13 Following a focused review of papers on "handoffs in the era of duty hours reform," DeRienzo et al, 14 Another type of physician-to-physician communication undergoing study is consultation with specialists. 13 However, studies have identified communication errors stemming from inadequate transmission of key pieces of clinical information and data about the patient 13,15 and insufficient faceto-face and/or written communication between cross-covering physicians 14 ; these errors increase the risk of adverse events.…”
Section: Physician-to-physician (Peer-to-peer) Communicationmentioning
confidence: 99%